Trade Effect of Sanitary and Phytosanitary (SPS) and Technical Barriers to Trade (TBT) on Indonesia's Shrimp Export - Khaliqi, Muhammad; Rifin, Amzul; Adhi, Andriyono Kilat (Indonesian Journal of Agricultural Research, 2018)
The development of the implementation of non-tariff measure policy, in the world market which has a trend, increased every year. There are seven (7) NTM policies mostly implemented in the international market. The most policy application is the implementation of Technical Barriers to Trade and Sanitary and Phytosanitary. Agricultural commodities both vegetables and live animal products are commodities mostly become subject to NTM policy in the form of SPS (Sanitary and Phytosanitary) and TBT (Technical Barriers on Trade) in the international market. Indonesia as an agricultural country that has advantages in agriculture and fisheries cannot avoid the implementation of SPS and TBT policies. This research was aimed to analyze the effect of SPS and TBT on Indonesia’s shrimp export using the gravity model. The results showed that the GDP of exporters and the exchange rate have negative influences on Indonesia’s shrimp exports. Meanwhile, the GDP of the importers and trade cost have positive influences on the export of shrimp Indonesia. while the SPS policy and TBT don’t affect Indonesia's exports of shrimp in the international market. This indicates that Indonesian shrimp exporters are able to quickly adjust the SPS and TBT policies applied by importing countries.